Acute Toxicity Test of Toman Fish Extract on Erythrocyte Number and Hemoglobin Level in Normal and Diabetic Wistar Rat Model - Amy Nindia Carabelly; Beta Widya Oktiani; Nurashfia Nurashfia; Maharani Laillyza Apriasari; Dewi Puspitasari (Berkala Kedokteran, 2023)
Abstract: Patients with diabetes mellitus (DM) may experience vascular impairment, wounds that emerged from dental practice require special attention in people who suffer from DM. Toman fish has the potential as an alternative medicine to accelerate the healing process in normal and diabetic wound. Erythrocyte and hemoglobin are two components of blood profile which can be used as the parameter to identify the effect of material toxicity. This study aims to test the acute toxicity of Toman fish extract at 16 mL/Kg BW dosage on the number of erythrocyte and the level of hemoglobin in normal and diabetic Wistar rat model after 14 days treatment. This is a true experimental study with post-test only and control group design. Samples were comprised of 21 male Wistar rats allocated to three different groups; normal rats given Toman fish extract (A), diabetic rats given Toman fish extract (B), and diabetic rats given BR2 feed only (C). The results showed that in group A, the number of erythrocytes was 8.67x106/mm3 and the level of hemoglobin was 17.30 g/dL. In group B, the number of erythrocytes was 7.39x106/mm3 and the level of hemoglobin was 16.32 g/dL. In group C, the erythrocyte number was 4.88x106/ mm3 and the hemoglobin level was 11.54 g/dL. It can be concluded that Toman fish extract at the dosage of 16 mL/Kg BW after 14 days administration is not toxic which was indicated by erythrocyte number and hemoglobin level in the blood of normal and diabetic Wistar rats models.